“Internet + Community” : Research on the Mode of Values Education in Colleges under the Complete Credit System - Lin, Zelong (Advances in Social Sciences Research Journal, 2019)
After the implementation of complete credit system, colleges gradually lead the class students to individualization, which is consistent with the characteristics of individualization in the Internet age. And the trend of “Internet community” constructed by Internet, from the earlier micro-blog to the current WeChat group or Moments, also provides us with new ideas on how to carry out values education for "individualized" college students under the complete credit system. The promotion of complete credit system in colleges and the trend of the "Internet community" enable colleges to effectively carry out values education of college students through a new way. Hence, colleges should, on one hand, pay more attention to the implicit education, understand and master the dissemination rules of the network platform, as well as utilize the new carrier of values education innovatively. On the other hand, colleges are also encouraged to construct the "Internet community" type education mode from the three dimensions of perfecting the community structure, adjusting the group mentality and emphasizing the guidance of public opinion.